Kosmologi sastra lisan Kalimantan dalam pendidikan nilai- nilai kepedulian lingkungan (tinjauan ekofeminisme spiritual) - Arditya, Arditya; Amalia, Puji Astuti; Hira, Tauhid; Azizah, Anisah (Fakultas Sastra, 2023)
The ignorance of morality by the youth causes the ignorance of environmental issues in Kalimantan. The purpose of this study is to strengthen the spiritual values of the youth in Kalimantan using ecofeminism oral literature to solve environmental issues in Kalimantan. This study uses qualitative approach with an ethnography design using data collection, classification and analyzation to get a comprehensive finding about the function of oral literature and its contribution to spiritual values in the perspective of environment, the data source is oral literature entitle Tanuhui, Betawol and Nyanyian Rakyat Tidung. The results of this study are immanence, represents the mandate of ancestors about the importance of nature. The second is interconnectedness, visualized dominantly in nyanyian rakyat tidung with mandate of humor, lust, intuition, intellect, and sympathy as part of nature. The third is the lifestyle where the femininity described as a way to take care the nature. Kata Kunci: ecofeminism, environmental care, spiritual, Kalimantan oral literature